Aluminum-lithium alloys : processing, properties, and applications - Prasad, N. Eswara; Gokhale, Amol A.; Wanhill, R. J. H. (Oxford : Butterworth-Heinemann, 2014)
Because lithium is the least dense elemental metal, materials scientists and engineers have been working for decades to develop a commercially viable aluminum-lithium (Al-Li) alloy that would be even lighter and stiffer than other aluminum alloys. The first two generations of Al-Li alloys tended to suffer from several problems, including poor ductility and fracture toughness; unreliable properties, fatigue and fracture resistance; and unreliable corrosion resistance. Now, new third generation Al-Li alloys with significantly reduced lithium content and other improvements are promising a revival for Al-Li applications in modern aircraft and aerospace vehicles. Over the last few years, these newer Al-Li alloys have attracted increasing global interest for widespread applications in the aerospace industry largely because of soaring fuel costs and the development of a new generation of civil and military aircraft. This contributed book, featuring many of the top researchers in the field, is the first up-to-date international reference for Al-Li material research, alloy development, structural design and aerospace systems engineering. Provides a complete treatment of the new generation of low-density AL-Li alloys, including microstructure, mechanical behavoir, processing and applicationsCovers the history of earlier generation AL-Li alloys, their basic problems, why they were never widely used, and why the new third generation Al-Li alloys could eventually replace not only traditional aluminum alloys but more expensive composite materialsContains two full chapters devoted to applications in the aircraft and aerospace fields, where the lighter, stronger Al-Li alloys mean better performing, more fuel-efficient aircraft.
Includes bibliographical references and index.
Keywords: Aluminum alloys